UJI KANDUNGAN SIKLAMAT PADA LEGEN JAMU GENDONG DI KELURAHAN SEKIP JAYA PALEMBANG - Irham Falahudin; Elfira Rosa Pane; Asri Arum Sari (Biota, 2016)
Legen is neutralizing bitter taste of herbs commonly used by herbalist. The sweet taste at the legen suspected of using artificial sweeteners. Cyclamate is one of the most common artificial sweetener used in food or beverages. In the world of education cyclamate included in class VIII SMP biology syllabus. The purpose of this research is in the legen contained cyclamate or not and the application of the experimental method (practicum) legen testing on student learning outcomes. Cyclamate content test study conducted in June 2015 and the application of the experimental method in August 2015. The method used in the testing of cyclamate is a deposition method while in the learning process used an experimental method (practicum). The results show that all samples tested legen containing cyclamate and exceeding the threshold is an average of the sample 1 (6 g / L), sample 2 (5.33 g / L), sample 3 (5.46 g / L), samples 4 (8.93 g / L) and sample 5 (6.26 g / L) while research using experimental method (practicum) menunjukka F count> F table (3.73> 2.66). The conclusion from this research that all traders use cyclamate exceeds the specified threshold and use of the experimental method affects the learning process on learning outcomes.